Economic, Socio-Cultural, and Environmental Impacts on Community Support for Tourism: A Case in Harapan Island, Kepulauan Seribu - Levyda, Levyda (Binus Business Review, 2020)
The research aimed to examine economic, socio-cultural, and environmental impacts on community support for tourism in Harapan Island, Kepulauan Seribu. Data were collected using a questionnaire. The population was the people of Harapan Island. Around 100 residents were selected as respondents through accidental sampling. Then, data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) version 3.2.8. Based on the hypothesis test, economic and socio-cultural factors significantly influence community support. Sociocultural factors have the most significant effect on community support. Meanwhile, environmental factors do not affect community support. The research contributes to the model of community support for the development of tourism on a small island. To increase community support, it is necessary to increase the income of the community, job opportunities, security, protection of traditional culture, and welfare.